On Partial Derivatives of the I-Function of r-Variables - (:unkn) unknown (INST MATH & MECHANICS AZERBAIJAN, 2020)
The object of this paper is to establish some formulas involving the partial derivatives of the Prasad's I-function of r-variables. On specializing the parameters, the results can be reduced to derivatives of H-function of r-variables, H-function of two variables. As a result, we have four corollaries concerning the multivariable H-function.
Keywords: I-function of two and several complex variables; multivariable H-functions; partial differentiation; GENERALIZED FRACTIONAL INTEGRALS; MULTIVARIABLE H-FUNCTION; PRODUCT